Bangladesh Climate-Smart Agriculture Investment Plan : Investment Opportunities in the Agriculture Sector’s Transition to a Climate Resilient Growth Path - World Bank Group (World Bank, Washington, DC, 2019)
Bangladesh’s agriculture sector is the country’s main source of food security, employment, and poverty alleviation. More than 70 percent of Bangladesh’s population and 77 percent of its workforce lives in rural areas. Nearly half of all Bangladeshi workers and two-thirds of workers in rural areas are directly employed in agriculture. About 87 percent of the nation’s rural households rely on agriculture for at least part of their income. With one of the fastest rates of productivity growth in the world (averaging 2.7 percent per year since 1995, second only to China), Bangladesh’s agriculture sector accounted for 90 percent of the country’s reduction in poverty between 2005 and 2010. This growth has also allowed the country to triple its rice production since it gained independence in 1971 and to halve its food deficit, and with it the number of malnourished people, since the mid-1990s. In 1991, nearly two-thirds of Bangladeshi children were underweight; today that number is less than one-third. Bangladesh faces growing demand for food and pressure from rapid land use change including significant losses of arable land. Population increases to an estimated 186 million by 2030 and 202 million by 2050, increasing income levels, and rapid urbanization at a rate of 3.5 percent annually 1 are expected to shift diets away from rice and wheat toward animal-based diets. At the same time, while Bangladesh produces almost all its own rice, current yield trends indicate production will not be able to satisfy growing demand for cereals (including rice), which is projected to increase 21 percent by 2030 and 24 percent by 2050. Given the increasing population density and continued loss of arable land caused by urbanization and other factors, enhancing the productivity of rice and other staple foods remains crucial. These trends suggest that Bangladesh must sustainably increase food production on far less arable land per capita to continue to strive for self-sufficiency in agricultural production. The World Bank considers climate-smart agriculture (CSA) a strategic priority investment in response to climate change in agriculture. The executive directors of the International Development Association (IDA) of the World Bank Group have recognized the need to address several concerning trends in the world’s poorest countries, including the growing demand for food, the unsustainable pressure of current agricultural practices on agricultural landscapes, the increasing threat of climate change to agricultural productivity, and agriculture’s significant contribution to greenhouse gas emissions.